Progress in Compact Antennas - Huitema, Laure; Huitema, Laure (IntechOpen, 2014)
Compact antennas are a subject of growing interest from industry and scientific community to equip wireless communicating objects. The need for high performance small antennas and RF front ends is the challenge for future and next generation mobile devices. This book brings the body of knowledge on compact antennas into a single comprehensive volume. It is designed to meet the needs of electrical engineering and physics students to the senior undergraduate and beginning graduate levels, and those of practicing engineers.
English
Keywords: Mobile phone technology; WAP (wireless) technology